Iridium ruthenium-based catalyst and preparation method thereof, and preparation method of membrane electrode

By preparing iridium ruthenium-based catalysts and using electrospinning and arc discharge technology to prepare fibrous nanorod materials, the problem of poor stability of existing catalysts at high potentials is solved, high activity and stability of the catalyst is achieved, and cost is reduced.

CN119640309APending Publication Date: 2025-03-18NINGBO ZHONGKEKE INNOVATION ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411808073.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

Smart Images

  • Figure CN119640309A_ABST
    Figure CN119640309A_ABST
Patent Text Reader

Abstract

The invention provides an iridium-ruthenium-based catalyst, a preparation method thereof and a preparation method of a membrane electrode, the iridium-ruthenium-based catalyst is used for water electrolysis, the iridium-ruthenium-based catalyst is a fibrous nanorod material, and the iridium-ruthenium-based catalyst comprises an iridium element, a ruthenium element and a transition metal element, the iridium ruthenium-based catalyst comprises the following components in percentage by weight: 30 to 70 percent of iridium element, 20 to 60 percent of ruthenium element, 0.1 to 5 percent of transition metal element and the balance of oxygen element, and the transition metal element comprises at least one of tungsten, titanium, niobium and tantalum, so that the activity and the stability of the catalyst are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy catalysis technology, and specifically to an iridium-ruthenium-based catalyst and a preparation method thereof, and a preparation method of a membrane electrode. Background Art

[0003] As a secondary energy source, hydrogen energy has the advantages of being clean, efficient, and easy to combine with renewable energy. It is an important way to solve current energy and environmental problems. Therefore, it is urgent to develop efficient and green hydrogen production technology to meet the growing market demand.

[0004] Compared with traditional hydrogen production technologies such as methane reforming and natural gas conversion, water electrolysis has the advantages of cleanliness, high efficiency, high hydrogen purity, and easy access to raw materials, and has attracted widespread attention. The water electrolysis process includes the oxygen evolution reaction (OER) at the anode and the hydrogen evolution reaction (HER) at the cathode. The OER is a four-electron reaction process, which has problems such as slow reaction kinetics and complex reaction pathways leading to large overpotentials, which is the main bottleneck limiting the efficiency and application of water electrolysis. At present, practical acidic OER catalysts can only use iridium or ruthenium-based precious metal catalysts, such as IrO2, RuO2, etc. However, a large number of studies have shown that although ruthenium-based catalysts have the best OER catalytic activity, they are prone to form soluble high-valent oxides (such as RuO4) at high potentials, resulting in poor stability and other problems; while iridium-based catalysts have excellent stability, but their OER catalytic activity is relatively poor compared to ruthenium-based catalysts, and the cost of iridium-based catalysts is much higher than that of ruthenium-based catalysts. Therefore, neither ruthenium-based nor iridium-based catalysts can take into account both catalytic activity and stability. Therefore, at present, there is an urgent need for a catalyst that can balance catalytic activity and stability. Summary of the invention

[0005] In view of this, the present application provides an iridium-ruthenium-based catalyst and a preparation method thereof, and a membrane electrode preparation method to improve the activity and stability of the catalyst.

[0006] The present application provides an iridium-ruthenium-based catalyst, which is used for water electrolysis. The iridium-ruthenium-based catalyst is a fibrous nanorod material. The iridium-ruthenium-based catalyst includes iridium, ruthenium, transition metal elements and oxygen. In terms of weight percentage, the iridium content is 30% to 70%, the ruthenium content is 20% to 60%, the transition metal content is 0.1% to 5%, and the balance is oxygen. The transition metal element includes at least one of tungsten, titanium, niobium and tantalum.

[0007] In one embodiment, the diameter of the fibrous nanorods is 2 to 10 nanometers, and the length of the fibrous nanorods is 50 to 100 nanometers.

[0008] The present application also provides a method for preparing an iridium-ruthenium-based catalyst, which is used to prepare the iridium-ruthenium-based catalyst as described above, comprising:

[0009] Dissolving an iridium-containing precursor, a ruthenium-containing precursor and a first organic polymer in a mixed solution of an organic alcohol and an organic acid to obtain a spinning solution sol, wherein the iridium-containing precursor includes at least one of chloroiridic acid, iridium trichloride and ammonium hexachloroiridate, the ruthenium-containing precursor includes at least one of ruthenium chloride, potassium chlororuthenate and sodium chlororuthenate, the first organic polymer includes one of PVP, PVB, PAN and PVA, the organic alcohol includes at least one of methanol, ethanol, ethylene glycol and benzyl alcohol, and the organic acid includes at least one of formic acid, acetic acid, oxalic acid and benzoic acid;

[0010] The spinning solution sol is placed in an electrospinning device and subjected to electrospinning treatment to form a first woven fabric having a fibrous shape;

[0011] performing a first heat treatment on the first woven fabric to form a second woven fabric;

[0012] Wrapping the second woven fabric outside a graphite electrode as a cathode of arc discharge and using a doping reactant as an anode of the arc discharge, performing arc discharge so that the doping reactant is deposited on the second woven fabric to form a third woven fabric, wherein the doping reactant includes a reactant containing at least one of tungsten, titanium, niobium, tantalum and oxides thereof;

[0013] performing a second heat treatment on the third spun fabric to form a fibrous iridium-ruthenium-based catalyst;

[0014] Among them, the iridium-ruthenium-based catalyst formed includes iridium element, ruthenium element, transition metal element and oxygen element. In terms of weight percentage, the iridium element content is 30% to 70%, the ruthenium element content is 20% to 60%, the transition metal element content is 0.1% to 5%, and the remainder is oxygen element. The transition metal element includes at least one of tungsten, titanium, niobium and tantalum.

[0015] In one embodiment, the molar ratio of the iridium-containing precursor to the ruthenium-containing precursor is (0.5-2): (2-0.5), the molar amount of the first organic polymer is 0.5-10 times the total molar amount of the iridium-containing precursor and the ruthenium-containing precursor, and the volume ratio of the organic alcohol to the organic acid is 1:1.

[0016] In one embodiment, the constant rate of the electrospinning process is 0.1 mL / h to 10 mL / h, and the voltage of the electrospinning process is 1 kV to 50 kV.

[0017] In one embodiment, the temperature of the first heat treatment is 100° C. to 180° C., and the time of the first heat treatment is 2 to 20 hours.

[0018] In one embodiment, the temperature of the second heat treatment is 200° C. to 800° C., and the time of the second heat treatment is 1 to 15 hours.

[0019] The present application also provides a method for preparing a membrane electrode, using the iridium-ruthenium-based catalyst as described above or the iridium-ruthenium-based catalyst prepared using the preparation method as described above, comprising:

[0020] Dispersing an iridium-ruthenium-based catalyst, a second organic polymer and a sulfonic acid resin in an organic alcohol solution to form a membrane electrode spinning solution, wherein the second organic polymer is PVP and PAN, and the organic alcohol solution is at least one of methanol, ethanol and isopropanol;

[0021] The spinning solution is placed in an electrospinning device and subjected to electrospinning treatment to form an iridium-ruthenium-based catalyst layer on one side of the proton exchange membrane and a platinum-carbon catalyst layer on the other side of the proton exchange membrane;

[0022] The proton exchange membrane containing the iridium-ruthenium-based catalyst layer and the platinum-carbon catalyst layer is subjected to hot pressing to form a PEM water electrolysis membrane electrode.

[0023] In one embodiment, the molar ratio of the iridium-ruthenium-based catalyst, PVP and PAN is 1:(0.2-0.5):(0.2-0.5).

[0024] In one embodiment, the mass ratio of the iridium-ruthenium-based catalyst to the organic alcohol is 1:(10-20).

[0025] The present application provides an iridium-ruthenium-based catalyst and a preparation method thereof, and a preparation method of a membrane electrode. The iridium-ruthenium-based catalyst is used for water electrolysis. The iridium-ruthenium-based catalyst is a fibrous nanorod material. The iridium-ruthenium-based catalyst includes iridium, ruthenium, transition metal elements and oxygen. In terms of weight percentage, the iridium content is 30% to 70%, the ruthenium content is 20% to 60%, the transition metal content is 0.1% to 5%, and the balance is oxygen. The transition metal element includes at least one of tungsten, titanium, niobium and tantalum to improve the activity and stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 It is a schematic flow chart of the preparation method of the iridium ruthenium-based catalyst provided in the present application;

[0028] Figure 2 It is a schematic flow chart of the method for preparing the membrane electrode provided in the present application;

[0029] Figure 3 Schematic diagram of XRD of the iridium ruthenium-based catalyst of Example 2 and the iridium oxide catalyst of the comparative example provided in the present application;

[0030] Figure 4 It is a schematic diagram of the CV curves of the iridium oxide catalyst prepared in Example 2 and the comparative example of the preparation method of the iridium ruthenium-based catalyst provided in the present application;

[0031] Figure 5 It is a schematic diagram of the OER curve of the iridium oxide catalyst prepared in Example 2 and the reference example of the preparation method of the iridium ruthenium-based catalyst provided in the present application;

[0032] Figure 6 It is a schematic diagram of the TEM morphology of Example 2 of the method for preparing an iridium-ruthenium-based catalyst provided in the present application;

[0033] Figure 7 It is a schematic diagram of membrane electrode activity test data of Example 2 of the method for preparing an iridium-ruthenium-based catalyst provided in the present application;

[0034] Figure 8 It is a schematic diagram of membrane electrode stability test data of Example 2 of the iridium-ruthenium-based catalyst preparation method provided in the present application. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present application are clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application. In the absence of conflict, the following embodiments and their technical features can be combined with each other.

[0036] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present application, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by a person skilled in the art to which this application belongs. The terms used herein are for the purpose of describing specific embodiments only and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more related listed items. The terms "connection", "electrical connection", and "electrical connection" used herein include any direct and indirect electrical or structural connection means. Therefore, if the text describes a first device coupled / connected / electrically connected to a second device, it means that the first device can be directly electrically / structurally connected to the second device, or indirectly electrically / structurally connected to the second device through other devices or connection means.

[0038] The present application provides an iridium-ruthenium-based catalyst, which is used for water electrolysis. The iridium-ruthenium-based catalyst is a fibrous nanorod material. The iridium-ruthenium-based catalyst includes iridium element, ruthenium element, transition metal element and oxygen element. In terms of weight percentage, the iridium element content is 30% to 70%, the ruthenium element content is 20% to 60%, the transition metal element content is 0.1% to 5%, and the balance is oxygen element. The transition metal element includes at least one of tungsten, titanium, niobium and tantalum.

[0039] In the present application, the iridium-ruthenium-based catalyst is composed of iridium, ruthenium, transition metal elements and oxygen elements, so that the electronic structure of iridium and ruthenium can be regulated by the transition metal elements to avoid the catalyst from easily forming soluble high-valent oxides at high potentials and affecting the catalytic activity, so that the catalyst can take into account both stability and activity.

[0040] The present application provides an iridium-ruthenium-based catalyst, which is used for water electrolysis. The iridium-ruthenium-based catalyst is a fibrous nanorod material. The iridium-ruthenium-based catalyst includes iridium element, ruthenium element, transition metal element and oxygen element. In terms of weight percentage, the iridium element content is 30% to 70%, the ruthenium element content is 20% to 60%, the transition metal element content is 0.1% to 5%, and the balance is oxygen element. The transition metal element includes at least one of tungsten, titanium, niobium and tantalum. Specifically, the catalyst appears as powder, and its microstructure is composed of fibrous nanorods. The iridium content can be 30%, 32%, 35%, 41%, 47%, 56%, 63%, 68.9% or 70%, etc., the ruthenium content can be 20%, 24%, 27.6%, 30.4%, 47.6%, 54%, 57.8% or 60%, etc., and the transition metal element content can be 0.1%, 0.6%, 1.4%, 2.5%, 3.8%, 4.7%, 4.98% or 5%, etc.

[0041] In the present application, the iridium-ruthenium-based catalyst is composed of iridium, ruthenium, transition metal elements and oxygen elements, so that the electronic structure of iridium and ruthenium can be regulated by the transition metal elements to avoid the catalyst from easily forming soluble high-valent oxides at high potentials and affecting the catalytic activity, so that the catalyst can take into account both stability and activity.

[0042] In the present application, by controlling the proportions of iridium, ruthenium and transition metal elements or iridium, ruthenium, transition metal elements and oxygen elements within the above range, it is further avoided that the catalyst easily forms soluble high-valent oxides at high potentials and affects the catalytic activity, so that the catalyst can take into account both stability and activity.

[0043] In one embodiment, the diameter of the fibrous nanorods is 2 to 10 nanometers, and the length of the fibrous nanorods is 50 to 100 nanometers. Specifically, the diameter of the fibrous nanorods can be 2 nanometers, 2.6 nanometers, 3.7 nanometers, 4.9 nanometers, 5.4 nanometers, 6.1 nanometers, 7.9 nanometers, 8.7 nanometers, 9.5 nanometers or 10 nanometers, and the length of the fibrous nanorods can be 50 nanometers, 54.2 nanometers, 67 nanometers, 71 nanometers, 76 nanometers, 84 nanometers, 97 nanometers or 100 nanometers, so as to further avoid the catalyst from easily forming soluble high-valent oxides at high potentials and affecting the catalytic activity, so that the catalyst can take into account both stability and activity.

[0044] See also Figure 1 , Figure 1 The present application also provides a method for preparing an iridium-ruthenium-based catalyst, which is used to prepare the iridium-ruthenium-based catalyst provided in the present application, comprising:

[0045] S11. Dissolve an iridium-containing precursor, a ruthenium-containing precursor and a first organic polymer in a mixed solution of an organic alcohol and an organic acid to obtain a spinning solution sol, wherein the iridium-containing precursor includes at least one of chloroiridic acid, iridium trichloride and ammonium hexachloroiridate, the ruthenium-containing precursor includes at least one of ruthenium chloride, potassium chlororuthenate and sodium chlororuthenate, the first organic polymer includes one of PVP, PVB, PAN and PVA, the organic alcohol includes at least one of methanol, ethanol, ethylene glycol and benzyl alcohol, and the organic acid includes at least one of formic acid, acetic acid, oxalic acid and benzoic acid.

[0046] Specifically, an iridium-containing precursor, a ruthenium-containing precursor and a first organic polymer are placed in a beaker, an organic alcohol and an organic acid are added, and a spinning solution sol is obtained after ultrasonic stirring and dissolving for 0.5-2.5 hours at room temperature; the iridium-containing precursor includes at least one of chloroiridic acid, iridium trichloride and ammonium hexachloroiridate, the ruthenium-containing precursor includes at least one of ruthenium chloride, potassium chlororuthenate and sodium chlororuthenate, the first organic polymer includes at least one of PVP (polyvinyl pyrrolidone), PVB (polyvinyl butyral), PAN (polyacrylonitrile) and PVA (polyvinyl alcohol), the organic alcohol includes at least one of methanol, ethanol, ethylene glycol and benzyl alcohol, and the organic acid includes at least one of formic acid, acetic acid, oxalic acid and benzoic acid. Optionally, the ultrasonic stirring and dissolving time can be 0.5 hours, 0.67 hours, 1 hour, 1.4 hours, 1.7 hours, 2.3 hours or 2.5 hours, etc.

[0047] In one embodiment, the molar ratio of the iridium-containing precursor to the ruthenium-containing precursor is (0.5-2):(2-0.5), the molar amount of the first organic polymer is 0.5-10 times the total molar amount of the iridium-containing precursor and the ruthenium-containing precursor, and the volume ratio of the organic alcohol to the organic acid is 1:1. Specifically, the molar ratio of the iridium-containing precursor to the ruthenium-containing precursor can be 0.5:2, 0.57:1.87, 0.89:1.64, 1:1.3, 1.2:1.1, 1.7:0.9, 1.9:0.6 or 2:0.5, the molar amount of the first organic polymer can be 0.5 times, 0.6 times, 1 times, 1.3 times, 1.8 times, 2.4 times, 3.7 times, 6.8 times, 8.6 times, 9.7 times or 10 times the total molar amount of the iridium-containing precursor and the ruthenium-containing precursor, and the volume ratio of the organic alcohol to the organic acid is 1:1.

[0048] In one embodiment, the spinning liquid sol obtained in step S11 is aged for 4-8 hours, that is, the obtained spinning liquid sol is left to stand or heated for 4 to 8 hours. Optionally, the aging time can be 4 hours, 4.6 hours, 5.3 hours, 6.7 hours, 7.8 hours or 8 hours, etc. The spinning liquid sol can arrange or cross-link the polymer chains, structures and solution viscosity in the spinning liquid sol to improve the stability of the spinning liquid sol in the spinning process and the quality of the fiber.

[0049] S12, placing the spinning solution sol into an electrospinning device, and performing electrospinning treatment to form a first woven fabric having a fibrous shape.

[0050] Specifically, the spinning solution sol is put into a syringe of an electrospinning device, and an electrospinning operation is performed at a set constant rate and a set voltage to obtain a first woven fabric having fibrous nanorods.

[0051] In one embodiment, the constant rate of electrostatic spinning is 0.1mL / h~10mL / h, and the voltage of electrostatic spinning is 1kV~50kV. Specifically, the constant rate of electrostatic spinning can be 0.1mL / h, 0.8mL / h, 1.3mL / h, 2.5mL / h, 3.7mL / h, 4.8mL / h, 5.9mL / h, 6.9mL / h, 7.8mL / h, 8.7mL / h, 9.8mL / h or 10mL / h, etc., and the voltage of electrostatic spinning can be 1kV, 2.4kV, 8.7kV, 10.8kV, 25.6kV, 36.9kV, 47.1kV or 50kV, etc. The constant rate and voltage of electrostatic spinning are set within this range so that the diameter of the fibrous nanorod catalyst formed is consistent, so that the catalyst formed subsequently has higher stability and fiber quality.

[0052] S13, performing a first heat treatment on the first woven fabric to form a second woven fabric.

[0053] Specifically, the first spun fabric formed in step S12 is placed in a muffle furnace and pre-oxidized at a certain temperature, that is, a second spun fabric is obtained after a first heat treatment to remove organic matter in the first spun fabric, leaving only oxides containing iridium and ruthenium, so that the subsequently formed catalyst has higher stability, fiber quality and catalytic activity.

[0054] In one embodiment, the temperature of the first heat treatment is 100°C to 180°C, and the time of the first heat treatment is 2 to 20 hours. Specifically, the temperature of the first heat treatment can be 100°C, 110°C, 123°C, 127°C, 137°C, 154°C, 171°C, 178°C or 180°C, and the time of the first heat treatment can be 2 hours, 7 hours, 10 hours, 15 hours, 18 hours or 20 hours. The temperature and time of the first heat treatment are set within this range to better remove organic matter in the first woven fabric, so that the subsequently formed catalyst has higher stability, fiber quality and catalytic activity.

[0055] S14. Wrap the second woven fabric around the graphite electrode as a cathode for arc discharge, use the doped reactant as an anode for arc discharge, and perform arc discharge to deposit the doped reactant on the second woven fabric to form a third woven fabric. The doped reactant includes a reactant containing at least one of tungsten, titanium, niobium, tantalum and their oxides.

[0056] Specifically, the second woven fabric is wrapped around the outside of the graphite electrode as the cathode of the arc discharge, and the doped reactant is used as the anode of the arc discharge. The working chamber of the arc discharge device is evacuated into a vacuum, and an inert gas is introduced for protection. The water cooling and cooling circulation system are turned on. After the system is stable, the feeding system is turned on to perform arc discharge. During the arc discharge process, the doped reactant on the anode continuously evaporates under the high temperature of the arc discharge and is deposited on the second woven fabric at the cathode to form a third woven fabric.

[0057] The doping reactant includes a simple substance or oxide of a transition metal element. Optionally, the doping reactant includes at least one of metal tungsten, metal titanium, metal niobium, metal tantalum, tungsten dioxide, titanium dioxide, niobium monoxide and tantalum dioxide, and the inert gas is selected from one of nitrogen and argon.

[0058] It is understandable that the amount of doping reactants can be controlled by the feed amount of the anode, so the required anode feed amount must be accurately calculated before arc discharge. In the present application, the oxide of the transition metal element is used as the anode of the arc discharge through at least one of tungsten dioxide, titanium dioxide, niobium monoxide and tantalum dioxide to ensure that the arc discharge can proceed normally, so that the doping reactant can be deposited on the second woven fabric during the arc discharge process to form a third woven fabric; if the oxide of other transition metal elements is selected, the arc discharge cannot proceed normally, and thus the catalyst with high stability, fiber quality and catalytic activity cannot be formed.

[0059] S15. Performing a second heat treatment on the third spun fabric to form a fibrous iridium-ruthenium-based catalyst. The formed iridium-ruthenium-based catalyst includes iridium element, ruthenium element, transition metal element and oxygen element. In terms of weight percentage, the iridium element content is 30% to 70%, the ruthenium element content is 20% to 60%, the transition metal element content is 0.1% to 5%, and the remainder is oxygen element. The transition metal element includes at least one of tungsten, titanium, niobium and tantalum.

[0060] Specifically, the third fabric deposited with transition metal elements is added to the quartz tube (the volume of the added third fabric cannot exceed 2 / 3 of the volume of the quartz tube), the program is set up on the tube furnace, and after the second heat treatment temperature is determined, oxidizing, reducing or inert gas is introduced into the quartz tube, and the tube furnace switch is turned on for the second heat treatment to obtain a one-dimensional iridium ruthenium-based catalyst.

[0061] In one embodiment, the temperature of the second heat treatment is 200°C to 800°C, and the time of the second heat treatment is 1-15 hours. Specifically, the temperature of the second heat treatment can be 200°C, 210°C, 228°C, 247°C, 289°C, 300°C, 412°C, 561°C, 670°C, 780°C, 790°C or 800°C, and the time of the second heat treatment can be 1 hour, 2.1 hours, 3.7 hours, 4.8 hours, 6.4 hours, 7.8 hours, 9.1 hours, 10.5 hours, 12.23 hours, 14 hours or 15 hours, etc.

[0062] In one embodiment, the oxidizing, reducing or inert gas includes at least one of air, oxygen, a hydrogen-argon mixture, carbon monoxide, ammonia, nitrogen and argon.

[0063] In one embodiment, after step S15, the iridium-ruthenium-based catalyst may be crushed, ground, and sieved to obtain a finished catalyst with uniform particle size.

[0064] In the present application, an iridium-ruthenium-based catalyst is formed by electrospinning and arc discharge, and the catalyst is configured to be composed of iridium, ruthenium, transition metal elements and oxygen elements, so that the electronic structure of iridium-ruthenium can be regulated by the transition metal element, while avoiding defects such as the inability to tightly combine between the transition metal element and the iridium-ruthenium atoms, uneven doping distribution of the transition metal element, or difficulty in controlling the doping content of the transition metal element, etc., that is, while improving the catalytic activity of the catalyst, the dissolution of ruthenium is reduced, that is, while improving the catalytic activity of the catalyst, the stability of the catalyst is improved, and the cost is reduced.

[0065] See also Figure 2 , Figure 2 The present application also provides a method for preparing a membrane electrode, which is prepared using the iridium-ruthenium-based catalyst provided by the present application or the iridium-ruthenium-based catalyst prepared using the preparation method provided by the present application, comprising:

[0066] S21. Dispersing the iridium-ruthenium-based catalyst, the second organic polymer and the sulfonic acid resin in an organic alcohol solution to form a membrane electrode spinning solution, wherein the second organic polymer is PVP and PAN, and the organic alcohol solution is at least one of methanol, ethanol and isopropanol.

[0067] S22, placing the spinning solution into an electrospinning device and performing electrospinning treatment to form an iridium-ruthenium-based catalyst layer on one side of the proton exchange membrane and a platinum-carbon catalyst layer on the other side of the proton exchange membrane.

[0068] The platinum-carbon catalyst layer can be formed by ultrasonic spraying.

[0069] S23, hot pressing the proton exchange membrane containing the iridium-ruthenium-based catalyst layer and the platinum-carbon catalyst layer to form a PEM water electrolysis membrane electrode.

[0070] In one embodiment, the molar ratio of the iridium-ruthenium-based catalyst, PVP and PAN is 1:(0.2-0.5):(0.2-0.5). Specifically, the molar ratio of the iridium-ruthenium-based catalyst, PVP and PAN can be 1:0.2:0.2, 1:0.25:0.23, 1:0.3:0.29, 1:0.37:0.4, 1:0.47:0.44 or 1:0.5:0.5, etc., to avoid the second organic polymer layer covering the iridium-ruthenium-based catalyst layer, thereby affecting the water electrolysis efficiency.

[0071] In one embodiment, the mass ratio of the iridium ruthenium based catalyst to the organic alcohol is 1:(10-20). Specifically, the mass ratio of the iridium ruthenium based catalyst to the organic alcohol can be 1:10, 1:12, 1:15, 1:17, 1:18 or 1:20.

[0072] In one embodiment, the hot pressing temperature is 100-120°C, the hot pressing pressure is 2-4Mpa, and the hot pressing time is 3-5min. Specifically, the hot pressing temperature can be 100°C, 103°C, 107°C, 110°C, 112°C, 114°C, 118°C or 120°C, etc., the hot pressing pressure can be 2Mpa, 2.3Mpa, 2.8Mpa, 3.6Mpa, 3.8Mpa or 4Mpa, etc., and the hot pressing time can be 3min, 3.7min, 4.1min, 4.6min, 4.9min or 5min.

[0073] In the present application, a catalyst formed by electrospinning and arc discharge and composed of iridium, ruthenium, transition metal elements and oxygen elements is used in the membrane electrode, so that the electronic structure of iridium and ruthenium can be regulated by the transition metal element, while avoiding defects such as the inability to tightly combine between the transition metal element and the iridium and ruthenium atoms, uneven distribution of the doping of the transition metal element, or difficulty in controlling the doping content of the transition metal element, etc., that is, while improving the catalytic activity of the catalyst, the dissolution of ruthenium is reduced, that is, while improving the catalytic activity of the catalyst, the stability of the catalyst is improved and the cost is reduced.

[0074] Example 1

[0075] 13.51g of ruthenium chloride, 8.23g of iridium trichloride and 8.37g of PVP were added to a 50mL small beaker; then, a mixed solution of 20mL of methanol and 20mL of formic acid was added, and the spinning solution sol was obtained after ultrasonic stirring and dissolving at room temperature for 1 hour; then, the spinning solution sol was allowed to stand and age for 4 hours, and then it was added to the syringe of the electrospinning device, and the injection rate was set to 5mL / h, and the working voltage was set to 20kV, and the electrospinning operation was performed. After the electrospinning operation was completed, the obtained first fibrous spun fabric was collected; then, it was placed in a muffle furnace, and the temperature of the muffle furnace was set to 500°C. After the first spun fabric was oxidized at this temperature for 16 hours, it was taken out, and the second spun fabric was obtained after the first heat treatment; then, the second spun fabric was wrapped around a graphite electrode as a cathode and placed in the working chamber of the arc discharge device, a metal tungsten wire was used as an anode and connected to the feeding system, the working chamber was evacuated, and a vacuum was passed through the muffle furnace. Enter inert gas protection, turn on the water cooling and cooling circulation system, turn on the feeding system after the water cooling and cooling circulation system are stable, and perform arc discharge operation. At this time, the tungsten at the anode continuously evaporates at high temperature and deposits on the second fabric at the cathode. At the same time, under the action of instantaneous high temperature, the tungsten completes the in-situ doping of iridium and ruthenium. After the tungsten wire is fed for 1 cm, the arc discharge is terminated to form a third fabric; then, the doped third fabric is placed in a quartz tube, placed in a tubular furnace, the heat treatment temperature is set to 500°C, a hydrogen-argon mixed gas is introduced into the quartz tube, the tubular furnace switch is turned on for heat treatment for 10 hours, and the catalyst after the second heat treatment is crushed, ground, and sieved to obtain an iridium-ruthenium-tungsten ternary catalyst. The formed iridium-ruthenium-tungsten ternary catalyst has an iridium content of 49.02%, a ruthenium content of 49.02%, and a tungsten content of 1.96%.

[0076] Example 2

[0077] Preparation of iridium ruthenium oxide catalyst:

[0078] 11.11g potassium chlororuthenate, 4.23g chloroiridic acid and 4.25g PAN were added to a 50mL beaker; then, a mixed solution of 10mL ethanol and 10mL acetic acid was added, and the spinning solution sol was obtained after ultrasonic stirring and dissolving at room temperature for 1 hour; then, the spinning solution sol was allowed to stand for 4 hours, and then it was added to the syringe of the electrospinning device, and the injection rate was set to 2mL / h, and the working voltage was set to 15kV, and the electrospinning operation was performed. After the electrospinning operation was completed, the obtained first fibrous spun fabric was collected; then, it was placed in a muffle furnace, and the temperature of the muffle furnace was set to 400°C. After the first spun fabric was oxidized at this temperature for 12 hours, it was taken out, and the second spun fabric was obtained after the first heat treatment; then, the second spun fabric after high-temperature oxidation was wrapped around a graphite electrode as a cathode and placed in the working chamber of the arc discharge device, and the filamentous titanium oxide was used as an anode and connected to the feeding system, and the working chamber was evacuated to a vacuum, and an inert gas was introduced. Gas protection, turn on the water cooling and cooling circulation system, turn on the feeding system after the water cooling and cooling circulation system are stable, and perform arc discharge operation. At this time, the titanium oxide of the anode continuously evaporates at high temperature and deposits on the woven fabric of the cathode. At the same time, under the action of instantaneous high temperature, the titanium completes the in-situ doping of iridium and ruthenium. The arc discharge is terminated after the titanium oxide wire is fed 0.25 cm (mass is 0.08 g). Then, the doped third woven fabric is placed in a quartz tube, placed in a tubular furnace, the second heat treatment temperature is set to 700°C, oxygen is introduced into the quartz tube, the tubular furnace switch is turned on for the second heat treatment for 12 hours, and the catalyst after the second heat treatment is crushed, ground, and sieved to obtain a titanium oxide-doped iridium ruthenium oxide catalyst, wherein the iridium content is 32.89%, the ruthenium content is 49.34%, the titanium content is 1.32%, and the oxygen content is 16.45%.

[0079] Preparation of membrane electrode:

[0080] The prepared titania-doped iridium ruthenium oxide catalyst was ultrasonically dispersed in 200 mL of isopropanol with 0.5 g of PAN, 0.5 g of PVP and 5 g of 20% perfluorosulfonic acid resin solution. The iridium ruthenium oxide catalyst was coated on one side of the proton exchange membrane by electrospinning, and the platinum carbon catalyst was ultrasonically sprayed on the other side. Then, the membrane electrode was hot-pressed at 120°C and 3 MPa pressure for 3 min to complete the membrane electrode assembly.

[0081] Example 3

[0082] 13.82g of sodium chlororuthenate, 8.36g of ammonium hexachloroiridate and 11.34g of PVA were added to a 50mL beaker; then, a mixed solution of 12mL of ethylene glycol and 12mL of oxalic acid was added, and the spinning solution sol was obtained after ultrasonic stirring and dissolving at room temperature for 1 hour; then, the spinning solution sol was allowed to stand for 6 hours, and then it was added to the syringe of the electrospinning device, and the injection rate was set to 0.6mL / h, the working voltage was set to 30kV, and the electrospinning operation was performed. After the electrospinning operation was completed, the obtained first fibrous fabric was collected and placed in a muffle furnace, and the temperature of the muffle furnace was set to 450°C. After the first fabric was oxidized at this temperature for 14 hours, it was taken out to obtain a second fabric; then, the second fabric after high-temperature oxidation was wrapped around a graphite electrode as a cathode and placed in the working chamber of the arc discharge device, and a metal niobium wire was used as an anode and connected to the feeding system, and the working chamber was evacuated to vacuum, and inert gas protection was introduced to the chamber, and the second fabric was oxidized at 450°C. The water cooling and cooling circulation system are turned on, and the feeding system is turned on after the water cooling and cooling circulation system are stable, and the arc discharge operation is performed. At this time, the niobium of the anode is continuously evaporated at high temperature and deposited on the second woven fabric of the cathode. At the same time, under the action of instantaneous high temperature, the niobium completes the in-situ doping of iridium and ruthenium. After the niobium wire is fed 0.5 cm (mass is 0.12 g), the arc discharge is terminated to obtain the third woven fabric; then, the doped third woven fabric is placed in a quartz tube, placed in a tubular furnace, the heat treatment temperature is set to 550° C., nitrogen is introduced into the quartz tube, the tubular furnace switch is turned on for a second heat treatment for 15 hours, and the catalyst after the second heat treatment is crushed, ground, and sieved to obtain a niobium suboxide doped iridium ruthenium oxide catalyst, wherein the iridium content is 47.81%, the ruthenium content is 34.15%, the niobium content is 1.65%, and the oxygen content is 16.39%.

[0083] Comparison example

[0084] Add 2.86g of chloroiridic acid into a 500mL beaker, add water to 300mL, and stir ultrasonically for 10 minutes; then, add a magnet into the beaker, and place the beaker in a water bath at 90℃ for magnetic stirring; then, dropwise add 100mL of sodium borohydride solution (2g of sodium borohydride dissolved in 100mL of water) into the beaker, and after the addition is complete, continue the reaction for 2 hours; then, after the reaction is completed, filter, place the filter cake in a 70℃ oven to dry for 12 hours, break and grind. Put the catalyst powder into a quartz tube, place the quartz tube in a tube furnace, set the heat treatment temperature to 500℃, and heat treat for 10 hours in an air atmosphere. After the heat treatment is completed, 1.2g of iridium oxide catalyst is obtained.

[0085] (1) XRD test: please refer to Figure 3 , Figure 3Schematic diagram of XRD of the iridium ruthenium-based catalyst of Example 2 and the iridium oxide catalyst of the comparative example provided in this application. X-ray diffraction was performed on the iridium ruthenium-based catalyst prepared in Example 2 and the iridium oxide catalyst prepared in the comparative example. Figure 3 It can be known that the iridium ruthenium-based catalyst prepared by embodiment 2 and the iridium oxide catalyst prepared by reference example all have only the diffraction peak of iridium oxide, do not see the diffraction peak of ruthenium, and the diffraction peak of iridium oxide shifts to the right simultaneously, meaning that ruthenium enters the lattice of iridium oxide.For other transition metal elements, due to its lower content, its diffraction peak intensity is weaker, has only a small peak or does not have peak on the collection of illustrative plates.By Scherrer formula, the iridium ruthenium-based catalyst average particle diameter that can be calculated is 4-6 nanometer, and the iridium oxide catalyst average particle diameter is 5-8 nanometer.

[0086] (2) Electrochemical test: please refer to Figure 4 and Figure 5 , Figure 4 It is a schematic diagram of the CV curves of the iridium oxide catalyst prepared in Example 2 and the comparative example of the preparation method of the iridium ruthenium-based catalyst provided in the present application; Figure 5 It is a schematic diagram of the OER curve of the iridium oxide catalyst prepared in Example 2 and the reference example of the preparation method of the iridium ruthenium based catalyst provided in the present application. Take 10 mg of each of the iridium ruthenium based catalyst prepared in Example 2 and the iridium oxide catalyst prepared in the reference example, dissolve them in 2.5 ml of pure water, add 0.2 ml of 5wt% Nafion solution and 0.3 ml of isopropanol, make an ink with a total volume of 3 ml, and ultrasonically disperse for 30 minutes. Take it and coat it on the platinum carbon working electrode, use the Ag / AgCl electrode as the reference electrode, and the platinum sheet as the counter electrode to form a classic three-electrode system. First, in a 0.1M HClO4 solution, after nitrogen is passed for 30 minutes, the one-dimensional iridium ruthenium based catalyst prepared in Example 2 and the iridium oxide catalyst prepared in the reference example are subjected to CV tests, and the following results are obtained: Figure 4 Schematic diagram. After that, in 0.5M H2SO4 solution, after nitrogen was passed for 30 minutes, the iridium ruthenium-based catalyst prepared in Example 2 and the iridium oxide catalyst prepared in the control example were subjected to OER test, and the following results were obtained: Figure 5 The data shown. Figure 4 and Figure 5 It can be seen that the CV of the iridium ruthenium-based catalyst is significantly larger than that of the iridium oxide catalyst, and at a current density of 10 mA / cm2, the oxygen evolution potential of the iridium ruthenium-based catalyst is 1.52 V, which is significantly lower than the oxygen evolution potential of the iridium oxide catalyst of 1.56 V. It can be seen that the OER catalytic activity of the iridium ruthenium-based catalyst is significantly better than that of the iridium oxide catalyst.

[0087] (3) TEM test: please refer to Figure 6 , Figure 61 is a schematic diagram of the TEM morphology of Example 2 of the method for preparing the iridium-ruthenium-based catalyst provided in the present application. The iridium-ruthenium-based catalyst prepared in Example 2 was subjected to transmission electron microscopy test and analysis, and the following was obtained: Figure 6 The data shown is a schematic diagram. Figure 6 It can be seen that the iridium ruthenium-based catalyst is a one-dimensional nanorod with a diameter of 2-10 nm and a length of 50-100 nm, and the particle size distribution of the iridium ruthenium-based catalyst is relatively uniform, indicating that the consistency of the iridium ruthenium-based catalyst is excellent.

[0088] (4) Membrane electrode test: please refer to Figure 7 and Figure 8 , Figure 7 It is a schematic diagram of membrane electrode activity test data of Example 2 of the method for preparing an iridium-ruthenium-based catalyst provided in the present application; Figure 8 The following is a schematic diagram of the membrane electrode stability test data of Example 2 of the iridium-ruthenium-based catalyst preparation method provided in this application. The membrane electrode prepared in Example 2 was placed in an electrolytic cell, and the activity of the membrane electrode was tested at 60°C and different current densities. Figure 7 The data schematic diagram shown in the figure shows that the stability test was carried out at 60°C and a current density of 2A / cm2, and the following results were obtained: Figure 8 The data diagram shown is as follows. Figure 7 and Figure 8 It can be seen that in the activity test, the voltage of the iridium ruthenium-based catalyst was 1.78V at a current density of 2A / cm2, and the activity level was higher than that of the conventional iridium oxide catalyst. In the stability test, the voltage was stabilized at about 1.78V at a current density of 2A / cm2 for 2000 hours, and the fluctuation did not exceed 20mV, indicating that the iridium ruthenium-based catalyst and membrane electrode of the present application have excellent stability.

[0089] The above descriptions are merely embodiments of the present application and are not intended to limit the patent scope of the present application. Any equivalent structural or equivalent process transformations made using the contents of the specification and drawings of the present application, such as the mutual combination of technical features between the embodiments, or direct or indirect application in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. An iridium-ruthenium-based catalyst, characterized in that The iridium-ruthenium-based catalyst is used for water electrolysis. The iridium-ruthenium-based catalyst is a fibrous nanorod material. The iridium-ruthenium-based catalyst includes iridium, ruthenium, transition metal and oxygen. In terms of weight percentage, the iridium content is 30% to 70%, the ruthenium content is 20% to 60%, the transition metal content is 0.1% to 5%, and the remainder is oxygen. The transition metal includes at least one of tungsten, titanium, niobium and tantalum.

2. The iridium-ruthenium-based catalyst according to claim 1, characterized in that The diameter of the fibrous nanorod is 2 to 10 nanometers, and the length of the fibrous nanorod is 50 to 100 nanometers.

3. A method for preparing an iridium-ruthenium-based catalyst, characterized in that: Used to prepare the iridium-ruthenium-based catalyst according to any one of claims 1 to 2, comprising: Dissolving an iridium-containing precursor, a ruthenium-containing precursor and a first organic polymer in a mixed solution of an organic alcohol and an organic acid to obtain a spinning solution sol, wherein the iridium-containing precursor includes at least one of chloroiridic acid, iridium trichloride and ammonium hexachloroiridate, the ruthenium-containing precursor includes at least one of ruthenium chloride, potassium chlororuthenate and sodium chlororuthenate, the first organic polymer includes one of PVP, PVB, PAN and PVA, the organic alcohol includes at least one of methanol, ethanol, ethylene glycol and benzyl alcohol, and the organic acid includes at least one of formic acid, acetic acid, oxalic acid and benzoic acid; The spinning solution sol is placed in an electrospinning device and subjected to electrospinning treatment to form a first woven fabric having a fibrous shape; performing a first heat treatment on the first woven fabric to form a second woven fabric; Wrapping the second woven fabric outside a graphite electrode as a cathode of arc discharge and using a doping reactant as an anode of the arc discharge, performing arc discharge so that the doping reactant is deposited on the second woven fabric to form a third woven fabric, wherein the doping reactant includes a reactant containing at least one of tungsten, titanium, niobium, tantalum and oxides thereof; performing a second heat treatment on the third spun fabric to form a fibrous iridium-ruthenium-based catalyst; Among them, the iridium-ruthenium-based catalyst formed includes iridium element, ruthenium element, transition metal element and oxygen element. In terms of weight percentage, the iridium element content is 30% to 70%, the ruthenium element content is 20% to 60%, the transition metal element content is 0.1% to 5%, and the remainder is oxygen element. The transition metal element includes at least one of tungsten, titanium, niobium and tantalum.

4. The method for preparing an iridium-ruthenium-based catalyst according to claim 3, characterized in that: The molar ratio of the iridium-containing precursor to the ruthenium-containing precursor is (0.5-2):(2-0.5), the molar amount of the first organic polymer is 0.5-10 times the total molar amount of the iridium-containing precursor and the ruthenium-containing precursor, and the volume ratio of the organic alcohol to the organic acid is 1:

1.

5. The method for preparing an iridium-ruthenium-based catalyst according to claim 3, characterized in that: The constant rate of the electrospinning treatment is 0.1 mL / h to 10 mL / h, and the voltage of the electrospinning treatment is 1 kV to 50 kV.

6. The method for preparing an iridium-ruthenium-based catalyst according to claim 3, characterized in that: The temperature of the first heat treatment is 100° C. to 180° C., and the time of the first heat treatment is 2 to 20 hours.

7. The method for preparing an iridium-ruthenium-based catalyst according to claim 3, characterized in that: The temperature of the second heat treatment is 200° C. to 800° C., and the time of the second heat treatment is 1 to 15 hours.

8. A method for preparing a membrane electrode, characterized in that: The method comprises: using the iridium-ruthenium-based catalyst described in any one of claims 1 to 2 or the iridium-ruthenium-based catalyst prepared by the preparation method described in any one of claims 3 to 7, comprising: Dispersing an iridium-ruthenium-based catalyst, a second organic polymer and a sulfonic acid resin in an organic alcohol solution to form a membrane electrode spinning solution, wherein the second organic polymer is PVP and PAN, and the organic alcohol solution is at least one of methanol, ethanol and isopropanol; The spinning solution is placed in an electrospinning device and subjected to electrospinning treatment to form an iridium-ruthenium-based catalyst layer on one side of the proton exchange membrane and a platinum-carbon catalyst layer on the other side of the proton exchange membrane; The proton exchange membrane containing the iridium-ruthenium-based catalyst layer and the platinum-carbon catalyst layer is subjected to hot pressing to form a PEM water electrolysis membrane electrode.

9. The method for preparing a membrane electrode according to claim 8, characterized in that: The molar ratio of the iridium-ruthenium-based catalyst, PVP and PAN is 1:(0.2-0.5):(0.2-0.5).

10. The method for preparing a membrane electrode according to claim 8, characterized in that: The mass ratio of the iridium-ruthenium-based catalyst to the organic alcohol is 1:(10-20).

Citation Information

Cited By

  • A preparation method of a ruthenium-manganese co-doped iridium dioxide anode catalyst

    CN122648988A